Intergenerational mobility, human capital transmission and the earnings of second-generation immigrants in Sweden - Mats Hammarstedt; Mårten Palme (Institute for the Study of Labor (IZA), 2006)
We compare the intergenerational earnings mobility of immigrants with natives in Sweden. We find an overall convergence in average earnings between immigrants and natives. This convergence hides a divergence in average earnings between groups of immigrants with different ethnic origins. We find that, on average, immigrants have a lower intergenerational earnings mobility, also (on average) within groups with similar ethnic backgrounds. Immigrants with a relatively low intergenerational earnings mobility increased their average earnings more in the second generation, thereby supporting the idea that low intergenerational earnings mobility can be interpreted as a high degree of intergenerational transmission of human capital.
Keywords: J15; J24; J61; J62; 330; intergenerational income mobility; intergenerational earnings correlation; Becker-Tomes model; ethnic capital; Humankapital; Intertemporale Einkommensverteilung; Generationenbeziehungen; Schweden